The Association of Body Mass Index and Mortality after Acute Ischemic Stroke - Skolarus, Lesli E. (Circ Cardiovasc Qual Outcomes, 2013)
BACKGROUND: The prevalence of severe obesity is rising in the US. Although mild to moderately elevated Body Mass Index (BMI) is associated with reduced mortality after acute ischemic stroke, less is known about severe obesity. METHODS AND RESULTS: Acute ischemic stroke patients (n=1,791) aged ≥45 years were identified from the bi-ethnic population-based Brain Attack Surveillance in Corpus Christi (BASIC) study from June 1, 2005 to December 31, 2010. Median follow-up was 660 days. BMI was abstracted from the medical record. Survival was estimated by BMI category (underweight normal-weight, overweight, class 1 obesity, class 2 obesity, and severe obesity) using Kaplan-Meier methods. Hazard ratios for the relationship between BMI modeled continuously and mortality were estimated from Cox regression models after adjusting for patient factors. The median BMI was 27.1 kg/m(2) (interquartile range, 23.7–31.2) and 56% were Mexican American. A total of 625 (35%) patients died during the study period. Persons with higher baseline BMI had longer survival in unadjusted analysis (P<0.01). After adjusting for demographics, stroke severity, stroke and mortality risk factors, the relationship between BMI and mortality was U-shaped. The lowest mortality risk was observed among patients with an approximate BMI of 35 kg/m(2), whereas those with lower or higher BMI had higher mortality risk. CONCLUSIONS: Severe obesity is associated with increased post-stroke mortality in middle-aged and older adults. Stroke patients with class 2 obesity had the lowest mortality risk. More research is needed to determine weight management goals among stroke survivors.